Doctoral Teaching and Mentoring in Digital Humanities: Changing Approaches to Graduate Pedagogy in Times of Multiple Crises. - Betik, Bailey; Cors, Alexander (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2023)
Focusing on graduate student education and professional development in the humanities, we examine how crises of the last few years – COVID-19, precarious employment and racial reckoning, among others – exposed iniquities in digital humanities (DH) and pedagogical training. This article explores how Emory Center for Digital Scholarship's (ECDS) outreach initiatives operated through and responded to recent years' crises post-2020. ECDS is committed to creating equitable opportunities for DH and pedagogical training for graduate students through long-term training, six-week intensives and an evolving open educational repository. The Digital Scholarship Training Program (DSTP) is a paid training programme for graduate students to learn digital skills through project-based learning. For students who cannot commit to a long-term practicum, ECDS offers two six-week intensives to provide equal opportunities for pedagogical training with emphasis on digital methods and tools. Currently, ECDS is building a repository hosted on WordPress to provide more flexible graduate training opportunities. By attuning ECDS offerings to varying levels of time and access, this suite of options aims to create equitable opportunities for graduate professional development that could serve as examples for other institutions. We conclude that DH methods and modalities can be deployed effectively to help address gaps in graduate student training.